Activated Platelets Induce Endothelial Cell Inflammatory Response in Psoriasis via COX-1. Issue 5 (May 2020) - Garshick, Michael S.; Tawil, Michael; Barrett, Tessa J.; Salud-Gnilo, Charissa M.; Eppler, Michael; Lee, Angela; Scher, Jose U.; Neimann, Andrea L.; Jelic, Sanja; Mehta, Nehal N.; Fisher, Edward A.; Krueger, James G.; et al.
Abstract : Objective: Patients with psoriasis have impaired vascular health and increased cardiovascular disease (CVD). Platelets are key players in the pathogenesis of vascular dysfunction in cardiovascular disease and represent therapeutic targets in cardiovascular prevention. The object of this study was to define the platelet phenotype and effector cell properties on vascular health in psoriasis and evaluate whether aspirin modulates the platelet-induced phenotype. Approach and Results: Platelets from psoriasis patients (n=45) exhibited increased platelet activation (relative to age- and gender-matched controls, n=18), which correlated with psoriasis skin severity. Isolated platelets from psoriasis patients demonstrated a 2- to 3-fold ( P <0.01) increased adhesion to human aortic endothelial cells and induced proinflammatory transcriptional changes, including upregulation of IL 8 (interleukin 8), IL1β, and Cox (cyclooxygenase)-2 Platelet RNA sequencing revealed an interferon signature and elevated expression of COX-1, which correlated with psoriasis disease severity ( r =0.83, P =0.01). In a randomized trial of patients with psoriasis, 2 weeks of 81 mg low-dose aspirin, a COX-1 inhibitor, reduced serum thromboxane (Tx) B2 and reduced brachial vein endothelial proinflammatory transcript expression >70% compared with the no-treatment group ( P <0.01). Improvement in brachial vein endothelial cell inflammation significantly correlated with change in serum TxB2 ( r =0.48, P =0.02). Conclusions: In patients with psoriasis, platelets are activated and induce endothelial cell inflammation. Low-dose aspirin improved endothelial cell health in psoriasis via platelet COX-1 inhibition. These data demonstrate a previously unappreciated role of platelets in psoriasis and endothelial cell inflammation and suggests that aspirin may be effective in improving vascular health in patients with psoriasis. Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT03228017. Abstract : Supplemental Digital Content is available in the text.